Analyzing the Far-reaching Effects and Causality: Investment, Corruption, Unemployment, and Economic Growth in Asia-Pacific Nations Over Time - Tama, M. Julian (Ministry of National Development Planning Republic of Indonesia/Bappenas, 2024)
This study investigates the causal connections and both short-term and long-term associations among corruption, investment, unemployment, and per capita economic growth across twenty-two Asia-Pacific nations spanning from 2012 to 2020. The research employs Granger causality and Vector Error Correction Model methodologies to tackle the research inquiries. The empirical results unveil bidirectional causality between corruption and per capita economic growth, whereas the unemployment rate and per capita economic growth share a unidirectional relationship. Conversely, no causal linkage is found among the remaining variables. In the short run, corruption has no significant impact on per capita economic growth and unemployment but does significantly and adversely affect the investment rate. On the other hand, in the long run, corruption significantly and negatively influences per capita economic growth. The investment rate and unemployment, in the long term, exhibit a substantial and positive influence on per capita economic growth. Thus, corruption serves as an obstacle to economic growth rather than a facilitator.